2022
DOI: 10.1186/s13046-022-02441-y
|View full text |Cite
|
Sign up to set email alerts
|

ARHGEF37 overexpression promotes extravasation and metastasis of hepatocellular carcinoma via directly activating Cdc42

Abstract: Background The extravasation capability of hepatocellular carcinoma (HCC) cells plays a vital role in distant metastasis. However, the underlying mechanism of extravasation in HCC lung metastasis remains largely unclear. Methods The expression of ARHGEF37 in human HCC specimens and HCC cell lines was examined by quantitative RT-PCR, western blot, and immunohistochemistry (IHC) analyses. The biological roles and mechanisms of ARHGEF37/Cdc42 in promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…One of the most well-researched Rho GTPase subfamilies is CDC42 (CDC42, RHOJ, and RHOQ) [ 25 ]. Cell division cycle 42 (CDC42) plays a vital regulatory role in cellular motility and polarization, which are closely related to the cytoskeleton and cell adhesion [ 26 28 ]. Considering that the differentially expressed genes regulated by TRIM56 knockdown were highly enriched in the Rho GTPase signaling and the motility-promoting effect of TRIM56 on glioma cells, we further assessed the effect of TRIM56 on CDC42 activation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most well-researched Rho GTPase subfamilies is CDC42 (CDC42, RHOJ, and RHOQ) [ 25 ]. Cell division cycle 42 (CDC42) plays a vital regulatory role in cellular motility and polarization, which are closely related to the cytoskeleton and cell adhesion [ 26 28 ]. Considering that the differentially expressed genes regulated by TRIM56 knockdown were highly enriched in the Rho GTPase signaling and the motility-promoting effect of TRIM56 on glioma cells, we further assessed the effect of TRIM56 on CDC42 activation.…”
Section: Resultsmentioning
confidence: 99%
“…CDC42 activation is directly regulated by various proteins, such as Rho guanine nucleotide exchange factor 37 (ARHGEF37) [ 26 ], IQ motif containing GTPase activating protein 1 (IQGAP1) [ 30 32 ], and N-myc downstream regulated 1 (NDRG1) [ 33 ]. In U87 and U251 cells, TRIM56 overexpression and knockdown increased and suppressed IQGAP1 expression, respectively, at protein level (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that FSCN1 promotes the invasion and metastasis of BLCA cells by directly binding to and inhibiting the TLN1, RAF1, CDC42, VAV2 and GRB2 mRNAs. RAF1 regulates the progression of endometrial cancer and hypopharyngeal cancer [27,28], CDC42 promotes metastasis in hepatocellular carcinoma [29], and TLN1 has a pro-metastatic function in prostate cancer [30]. Therefore, we hypothesize that FSCN1 forms an RBP regulatory network with multiple mRNAs, which is the molecular basis of the metastasis in various tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Though AM is benign, it shares certain characteristics with cancers, such as the ability to invade and metastasize. Growing evidence indicates that Rho GTPases, one of the most important regulators of cytoskeletal protein ( Guan et al, 2020 ), play a crucial role in the abnormal motility of tumor cells ( Kim et al, 2022 ; Qiu et al, 2022 ; Zhang et al, 2022 ). The Rho GTPases consist of 60 members and can be divided into multiple subfamilies ( Jansen et al, 2018 ; Clayton and Ridley, 2020 ).…”
Section: Discussionmentioning
confidence: 99%